2012
DOI: 10.1158/1535-7163.mct-12-0580
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Basis for Overcoming Platinum Resistance Using Copper Chelating Agents

Abstract: Platinum (Pt)-based antitumor agents are widely used in cancer chemotherapy. Drug resistance is a major obstacle to the successful use of these agents because once drug resistance develops, other effective treatment options are limited. Recently, we have conducted a clinical trial using a copper (Cu)-lowering agent to overcome Pt drug resistance in ovarian cancer patients and the preliminary results are encouraging. In supporting this clinical study, using three pairs of cisplatin (cDDP)-resistant cell lines a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 32 publications
(52 reference statements)
6
73
0
Order By: Relevance
“…Previous Expression of the copper transporters hCtr1, ATP7A and ATP7B is associated with the response to chemotherapy and survival time in patients with resected non-small cell lung cancer studies have revealed that copper ions and platinum drugs may share the same transport system in the cell (12)(13)(14). A different study demonstrated that copper ion transport proteins not only participate in the metabolism of the copper ions, but also maintain the balance of copper and are ultimately associated with the development of cisplatin resistance (15). In particular, human copper transporter 1 (hCtr1) is the major copper influx transporter and also transports cisplatin and cisplatin analogues into cells (13), while two other copper transporters, consisting of copper-transporting p-type adenosine triphosphatase 1 (ATP7A) and 2 (ATP7B), regulate the efflux of cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Previous Expression of the copper transporters hCtr1, ATP7A and ATP7B is associated with the response to chemotherapy and survival time in patients with resected non-small cell lung cancer studies have revealed that copper ions and platinum drugs may share the same transport system in the cell (12)(13)(14). A different study demonstrated that copper ion transport proteins not only participate in the metabolism of the copper ions, but also maintain the balance of copper and are ultimately associated with the development of cisplatin resistance (15). In particular, human copper transporter 1 (hCtr1) is the major copper influx transporter and also transports cisplatin and cisplatin analogues into cells (13), while two other copper transporters, consisting of copper-transporting p-type adenosine triphosphatase 1 (ATP7A) and 2 (ATP7B), regulate the efflux of cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to play a major role in CisPt uptake and cytotoxicity [3]. The absence of Ctr1 render cells resistant to CisPt [4] whereas patients with high levels of Ctr1 in their tumors responded better to platinum drug treatment [5]. ATP7A and ATP7B are homologous Cu-transporting ATPases positioned in the trans-Golgi network.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, several studies have reported that expression levels of hCtr1 in tumors are significantly correlated with better treatment outcomes in terms of increased progression-free survival (PFS) time and overall survival (OS) times in patients treated with Pt-based therapeutics [4750]. In some tumor types, elevated expression of hCtr1 is intrinsically sensitive to Pt-based treatment, suggesting that hCtr1 levels may be a predictive marker for effectiveness of Pt drug in cancer treatment.…”
Section: Mechanisms Of Cddp Transportmentioning
confidence: 99%
“…(see below). However, correlations between PFS or OS and ATP7 and ATP7B expression in ovarian cancer patients [50] and lung cancer patients were not as significant [47]. Moreover, expression of hCtr1, but not ATP7A or ATP7B, can be readily upregulated by manipulations of cellular Cu contents (see below).…”
Section: Mechanisms Of Cddp Transportmentioning
confidence: 99%